PENGARUH BRAND IMAGE DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE SAMSUNG (Studi Pada Mahasiswa Jurusan Manajemen Fakultas Ekonomi dan Bisnis UNISMA) - Wahyu Anggar Saputra; Rois Arifin; M Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT  This research is based on the tight competition of electronic products in the form of mobile phones with. As well as how the company can survive in determining the position B and get the spotlight from consumers (especially Samsung products). This study aims to (1) find out and analyze the influence of the simultaneous brand image and word of mouth on the Samsung mobile purchasing decision process and (2) to find out and analyze the influence of partial brand image and word of mouth on the purchase decision of Samsung mobile phones. The population in this study were students of the Faculty of Economics and Business Management Department and obtained 82 respondents with technical testing of validity, reliability, t test and F test processed into the regression equation as follows: Y = 3.315 + 0.449 + 0.332 + e. Where is the brand image variable as X1, word of mouth as X2 and purchase decision as variable Y. The results show that there is a significant influence both partially and simultaneously brand image and word of mouth variables on the purchase decision of Samsung brand mobile phones.  Keywords : Brand Image, Word Of Mouth and Purchase Decision.